Pengaruh Kemampuan Kerja, Motivasi Dan Komitmen Organisasi Terhadap Kinerja Pegawai Kantor Camat Manduamas Kabupaten Tapanuli Tengah - Ardi Ansyah Harahap; Vicky Yansen Jefriando; Wenny Wahyuni; Rizky Bagustianto (Jurnal Prodi Fakultas Ekonomi-UISU, 2022)
This formula research internal issue is how influence of job ability on employees performance. How influence of motivation on employees performance. How influence of organization commitment on employees performance. How influence of job ability, motivation and organization commitment on employees performance. This research target is to for know influence and analyze of job ability on employees performance. For know influence and analyze motivation on employees performance. For know influence and analyze organization commitment on employees performance. For know influence and analyze job ability, motivation and organization commitment on employees performance. Sample in this research amount to 34 employees. Technique analyze data which used in this research is analysis of regresi multiple linear. This research result explain of job ability effect positive and significant on employees performance. Motivation effect positive and significant on employees performance. Organization commitment effect positive and significant on employees performance .Job ability, motivation and organization commitment effect and positive and significant on employees performance